Isolation, Identification, and Antimicrobial Susceptibility Testing of Bacterial Pathogens at Chronic Sore Throat Patients Attending Outpatient Department of a Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2022)
Abstract: Sore throat manifested by throat pain is a troublesome issue or discomfort for which physicians are used to prescribing antibiotics, but most often, it is found that the patient is not responding to the drug, which gives rise to the question of drug-resistant or whether there is any infection at all? Nonspecific throat pain also imparts serious public health problems. Self-medication, inadvertent and inadequate doses of antibiotics frequently prescribed by both village doctors and registered MBBS doctors is really a public health problem in developing countries like Bangladesh.Aims: The aims of this study are to isolate the common organisms in chronic throat infection and to find out the effectiveness of various commonly used antibiotics.Methods: The samples were collected randomly from sore throat patients via a throat swab in 5 ml of 1% sterilized saline water, and the sample was brought to the laboratory and was inoculated within two hours in both blood agar and nutrient agar (NA) media and samples were incubated at 37°C overnight. Then pure colonies were transferred to Mueller Hinton agar, and antimicrobial susceptibility testing was done by the Kirby Bauer disc diffusion method.Results: A total of 27(24%) out of 111 samples yield positive growth. In a large number of samples, 84 (76%) did not show any isolation of the pathogenic organism. The predominant organism is a Staphylococcus aureus (55.55%). Thereafter, streptococcus (18.51%), Klebsiellapneumone (14.81%)and Pseudomonas (11.11%).Amoxiclav is the most resistant drug, along with cefuroxime, azithromycin, and doxycycline, respectively. Levofloxacin and ciprofloxacin show intermediate sensitivity. The most sensitive drug used in chronic sore throat found is linezolid though not frequently used, and other sensitive drugs are moxifloxacin and ceftriaxone.Conclusion: Throat pain or soreness does not always indicate that patient has been infected by bacteria. Rationale and ethical prescription, as well as microbiological sensitivity testing, are considered to avoid drug-resistant strains.TAJ 2022; 35: No-1: 25-31